"The Genteel Tradition in American Philosophy" as a Valedictory Indictment of the United States - Juan José Cruz Hernández (Miscelánea: A Journal of English and American Studies, 1996)
This article aims to point out some intellectual and cultural elements that constructed Santayana’s most famous lecture and phrase. Written in the aftermath of the events that transformed the United States in the turn of the century, “The Genteel Tradition in American Philosophy” is more than an elaborate literary critique. It contains Santayana’s objections to authors whose canonized aesthetics had provided ethical alibi for two defining features of the United States in those years: social injustice at home and a foreign policy based on the right of might. This helps us explain Santayana’s decision to leave America not just as the pose of a aesthetician; rather, it foresees the discontent that the American intelligentsia would widely express the following decade. Finally, some comment is offered on the limitations of “The Genteel Tradition” as a tract; our 80-year hindsight permits us assess the shortcomings of early twentieth-century liberal formulas to overcome the evils bred by nineteenth-century capitalism.